2018
DOI: 10.1111/jdv.14775
|View full text |Cite
|
Sign up to set email alerts
|

Role of T helper 17 cells and T regulatory cells in alopecia areata: comparison of lesion and serum cytokine between controls and patients

Abstract: These results showed significantly high Th17 cytokines in both lesion and serum in AA patients, which may highlight a functional role of these cytokines in the pathogenesis of AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 20 publications
3
70
1
Order By: Relevance
“…Studying scalp biopsies and serum samples from AA patients, they found out that lesional IL‐17, IL‐22, and serum IL‐1, IL‐17, TNF‐α, and TGF‐β were significantly higher in AA patients than in controls. Moreover, they demonstrated that there were positive correlations between lesional and serum IL‐17 and disease severity …”
Section: Il‐17 and Autoimmune Skin Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying scalp biopsies and serum samples from AA patients, they found out that lesional IL‐17, IL‐22, and serum IL‐1, IL‐17, TNF‐α, and TGF‐β were significantly higher in AA patients than in controls. Moreover, they demonstrated that there were positive correlations between lesional and serum IL‐17 and disease severity …”
Section: Il‐17 and Autoimmune Skin Diseasesmentioning
confidence: 99%
“…Recent evidences highlighted the role of both Th17 cells and T regulatory (Treg) cells in the pathogenesis of alopecia areata (AA) . Loh et al .…”
Section: Il‐17 and Autoimmune Skin Diseasesmentioning
confidence: 99%
“…Depression and anxiety experienced by patients with AA were measured using the Hospital Anxiety and Depression Scale (HADS) questionnaire. 37 HADS scores were interpreted as no depression/anxiety (0-7), mild depression/anxiety (8-10), moderate depression/anxiety (11)(12)(13)(14) and severe depression/ anxiety (15)(16)(17)(18)(19)(20). Severity of Alopecia Tool (SALT) 38 scores were calculated to assess severity of hair loss, and patients were stratified accordingly: inactive disease (S0), patchy hair loss (S3 ≥ S4a), severe hair loss (S4b ≥ S5, alopecia universalis and totalis).…”
Section: Clinical Datamentioning
confidence: 99%
“…IFN‐γ and interleukin (IL)‐15 are crucial for potentiating the activity of CD8 + T cells and natural killer cells in AA . Concentrations of circulating IL‐6, tumour necrosis factor (TNF)‐α, IL‐17A, IL‐21, IL‐22 and IL‐23 are elevated in patients with AA . In the skin, molecular profiling reveals dysregulation in cytokines associated with type 1 and type 2 inflammation, while also indicating altered expression of IL‐23 .…”
mentioning
confidence: 99%
“… In contrast, studies in humans have shown an increase in T reg. However, the majority of studies in humans have been conducted via flow cytometry on peripheral blood . There are limited data addressing T reg in the local cutaneous environment.…”
Section: Introductionmentioning
confidence: 99%